Sandwich-structured hybrid capacitor positive electrode and preparation method thereof
By using a sandwich structure design in the positive electrode of the hybrid capacitor and using micropores and large pore graphene to coat the hierarchical porous structure, the low specific surface area and low conductivity problems caused by stacking are solved, and the improvement of high energy density and high power density is achieved.
Patent Information
- Application Number
- CN202411315542.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-03-07
AI Technical Summary
The existing hybrid capacitor positive electrode materials are prone to stacking during electrode preparation, resulting in low specific surface area and low conductivity, limiting the increase in energy density and power density.
The positive electrode of the hybrid capacitor using a sandwich structure is formed by coating the first slurry layer, the second slurry layer and the first slurry layer again on the current collector to form a micropore and large pore graphene coated with a graded porous structure.
It effectively alleviates the low specific surface area and low conductivity problems caused by stack agglomeration, improves the energy density and power density of hybrid capacitors, and reduces internal resistance.
Smart Images

Figure CN119581231A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitors, and in particular to a positive electrode of a hybrid capacitor with a sandwich structure and a preparation method thereof. Background Art
[0002] Lithium-ion batteries and supercapacitors are the two most important energy storage devices. The low power density of lithium-ion batteries and the low energy density of supercapacitors greatly limit their wider applications. Therefore, it is of great significance to unify the characteristics of batteries and capacitors into one device to achieve both energy and power density for expanding the application of energy storage devices.
[0003] The composite energy storage technology of batteries and capacitors is divided into external parallel hybrid mode (device level) and internal parallel hybrid mode (electrode level). Although the combination of lithium-ion batteries and supercapacitors in external parallel has been adopted in the fields of hybrid new energy vehicles and new energy power grids to meet the needs of power and energy at the same time, it has the disadvantages of insufficient power density, excessive weight and volume, complicated power management system and high cost. Compared with external parallel connection, internal parallel connection has both lithium-ion energy storage and double-layer energy storage mechanism in the same electrode, which not only overcomes the disadvantage of insufficient capacity of pure activated carbon electrodes and further improves specific energy, but also ensures the consistency of monomers and reduces the complexity of power management system.
[0004] Carbon-based materials with high specific surface area are often used as positive electrode materials for capacitors. They mainly rely on the double electric layer formed at the interface between the electrode and the electrolyte to store energy. Since the surface adsorption and desorption energy storage of activated carbon is much lower than the capacity density of the negative electrode bulk energy storage, the lower capacity positive electrode is the main factor limiting the energy density of hybrid capacitors. Since graphene is a two-dimensional ductile state of graphite, it has a large specific surface area and unparalleled electrical conductivity. As a single-layer sheet material, it can not only ensure the uniform, continuous and dense surface coating effect compared to carbon black and carbon nanotubes, resulting in a significant improvement in electronic conductivity, but also can be embedded between the particles of the positive electrode material to effectively improve the bulk conductivity, thereby bringing about a breakthrough in the power performance of lithium-ion batteries. However, graphene stacking, high ion migration resistance, low porosity, and small effective specific surface area are technical problems that need to be urgently solved in the development of graphene-based hybrid supercapacitors.
[0005] Publication No.: 102938325A, hybrid capacitor and preparation method thereof. The positive electrode material is a graphene mixture with a mass ratio of graphene and nickel-cobalt-manganese ternary material of 1:0.1~1, which reduces the internal resistance of the overall capacitor and enables the hybrid capacitor to form a higher specific capacitance. Graphene is used to form a double electric layer on the surface, and the nickel-cobalt-manganese ternary material is used for ion embedding-de-embedding storage capacity. However, graphene is a nanomaterial and is prone to stacking during the electrode preparation process. In practical applications, dispersion is more important than anything else, and excessive addition will only reduce the amount of electrode active material used, which will lead to a low capacity of the hybrid capacitor. Summary of the invention
[0006] The technical problem to be solved by the embodiments of the present invention is to provide a sandwich structured hybrid capacitor positive electrode and a preparation method thereof, so as to alleviate the problems of low specific surface area and low conductivity caused by stacking agglomeration and improve energy density and power density.
[0007] In order to solve the above technical problems, an embodiment of the present invention proposes a sandwich structure hybrid capacitor positive electrode, including a current collector, on which a first slurry layer, a second slurry layer, and a first slurry layer are sequentially coated, wherein: The first slurry of the first slurry layer includes the following components by mass: 84-96 parts of nano single crystal positive electrode material, 1-3 parts of first graphene, 1-6 parts of first conductive agent and 2-7 parts of first binder; The second slurry of the second slurry layer includes the following components in parts by mass: 80-90 parts of carbon material, 1-5 parts of second graphene, 4-7 parts of second conductive agent and 5-8 parts of second binder.
[0008] Furthermore, the nano single crystal positive electrode material includes LiFePO 4 、LiCoO 2 、LiNi x Co y Mn z O 2 、LiNi x Co y Al z O 2 One or more of, x+y+z=1, 0.2≤x≤0.95, 0.05≤y≤0.4, 0.05≤z≤0.5.
[0009] Furthermore, the first graphene and the second graphene both have a specific surface area of 400 to 2000 m 2 / g of graphene.
[0010] Furthermore, the first graphene of the first slurry is coated on the outside of the nano single crystal positive electrode material, and the second graphene of the second slurry is coated on the outside of the carbon material.
[0011] Furthermore, the first graphene is microporous graphene, the second graphene is macroporous graphene, and the pores of the first graphene are smaller than the pores of the second graphene.
[0012] Furthermore, the coating thickness of the first graphene and the second graphene are both less than 1000nm.
[0013] Furthermore, the first conductive agent and the second conductive agent are acetylene black, conductive carbon black or carbon nanotubes, the first binder is polyvinylidene fluoride, the second binder is a mixture of one or more of styrene-butadiene rubber, acrylonitrile multipolymer and polytetrafluoroethylene, and the current collector is carbon-coated aluminum foil or corroded aluminum foil.
[0014] Accordingly, an embodiment of the present invention further provides a method for preparing a positive electrode of a hybrid capacitor with a sandwich structure, comprising the following steps: S1: uniformly coating the first slurry on one side of the current collector to form a first slurry layer with a coating thickness of 30-50 μm; S2: uniformly coating the second slurry on the surface of the first slurry layer to form a second slurry layer with a coating thickness of 50-80 μm; S3: The first slurry is uniformly coated on the surface of the second slurry layer again, and the coating thickness is 30-50 μm; S4: After drying on one side, repeat steps S1 to S3 to coat the other side of the current collector to obtain a positive electrode sheet with a sandwich structure coated on both sides; S5: The obtained double-sided coated sandwich structure positive electrode sheet is vacuum dried at 80° C. for 3 h, and the thickness of the positive electrode sheet is rolled to 100-200 μm at a pressure of 5-20 MPa to obtain a hybrid capacitor positive electrode with a composite sandwich structure.
[0015] Further, the first slurry is prepared according to the following steps: S11: Bake the powder of the nano single crystal positive electrode material and the first conductive agent at 120° C. for more than 8 hours before use to ensure accurate weight measurement; S12: Weigh 84-96 parts of nano single crystal positive electrode material and 1-3 parts of first graphene by mass to form active material mixture A; S13: dissolving the first binder with N-methylpyrrolidone, stirring and dispersing, and evacuating the mixture to a transparent solution for standby use; S14: adding the first conductive agent to the solution and dispersing at high speed for 2-3 hours; S15: Add active material mixture A three times and disperse at high speed for 4-6 hours to prepare a first slurry, which is passed through a 200-mesh sieve for later use.
[0016] Further, the second slurry is prepared according to the following steps: S21: baking the carbon material and the second conductive agent powder at 140° C. for more than 4 hours before use to ensure accurate weight measurement; S22: Weigh 80-90 parts of carbon material and 1-5 parts of second graphene by mass to form an active material mixture B; S23: Weigh 5 to 8 parts of the second binder, add it to pure water, and disperse it in a mixer at a speed of 100 to 500 r / min until the second binder is completely dispersed in the water; S24: Add the second conductive agent, soak evenly at low speed, and disperse at high speed for 2h; S25: Add active material mixture B gradually in three times and disperse at high speed for 4-6 hours; S26: The second slurry is configured to pass through a 200-mesh sieve for standby use.
[0017] The beneficial effects of the present invention are as follows: the present invention performs gradient coating of the first slurry and the second slurry to obtain a hybrid capacitor positive electrode with a microporous and macroporous graphene-coated graded porous structure, and effectively alleviates the problems of low specific surface area and conductivity caused by stacking agglomeration by controlling the distribution of the electrode microstructure, which is conducive to the preparation of a hybrid capacitor with lower impedance and both high energy density and high power density. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a charging rate curve diagram of the hybrid supercapacitor of Example 5 of the present invention.
[0019] Figure 2 4 is a discharge rate curve of the hybrid supercapacitor of Example 5 of the present invention.
[0020] Figure 3 3.8V / 8C graph of the cycle life of the hybrid supercapacitor of Example 5 of the present invention.
[0021] Figure 4 4.2V / 5C graph of the cycle life of the hybrid supercapacitor of Example 5 of the present invention.
[0022] Figure 5 It is a structural schematic diagram of the sandwich structure of the present invention.
[0023] Description of Figure Numbers The first slurry layer 1 and the second slurry layer 2. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments may be combined with each other. The present invention is further described in detail below in conjunction with the drawings and specific embodiments.
[0025] The positive electrode of the sandwich structure hybrid capacitor of the embodiment of the present invention includes a current collector, and the first slurry layer, the second slurry layer, and the first slurry layer are sequentially coated on both sides (front and back) of the current collector. Figure 5 .
[0026] The first slurry includes the following components by mass: 84-96 parts of nano single crystal positive electrode material, 1-3 parts of first graphene, 1-6 parts of first conductive agent and 2-7 parts of first binder. The first graphene-coated nano single crystal positive electrode material of the first slurry, The second slurry includes the following components by mass: 80-90 parts of carbon material, 1-5 parts of second graphene, 4-7 parts of second conductive agent, and 5-8 parts of second binder. The second graphene of the second slurry is coated with carbon material. The coupling edge sites on the graphene framework of the present invention are enriched with nano-single crystal positive electrode material nanoparticles; a mutually interpenetrating hierarchical pore structure is constructed on a microscopic scale, which effectively alleviates the problem of low specific surface area and conductivity caused by stacking agglomeration. In this field, the carbon material is generally activated carbon.
[0027] As an embodiment, the nano single crystal positive electrode material includes LiFePO 4 、LiCoO 2 、LiNi x Co y Mn z O 2 、LiNi x Co y Al z O 2 One or more of, x+y+z=1, 0.2≤x≤0.95, 0.05≤y≤0.4, 0.05≤z≤0.5.
[0028] As an embodiment, the first graphene and the second graphene both have a specific surface area of 400 to 2000 m 2 / g of graphene.
[0029] As an implementation mode, the first graphene is microporous graphene, the second graphene is macroporous graphene, and the pores of the first graphene are smaller than the pores of the second graphene.
[0030] As an implementation mode, the coating thickness of the first graphene and the second graphene are both less than 1000 nm.
[0031] As an embodiment, the first conductive agent and the second conductive agent are acetylene black, conductive carbon black or carbon nanotubes, the first binder is polyvinylidene fluoride (PVDF), the second binder is a mixture of one or more of styrene-butadiene rubber, acrylonitrile multipolymer and polytetrafluoroethylene, and the current collector is carbon-coated aluminum foil or corroded aluminum foil. The graphene of the present invention generates a distributed three-dimensional pore structure inside the activated carbon.
[0032] The conductive agent of the present invention is in the form of particles, which can be well filled into the gaps between the particles coated with graphene, but the surface coverage is not perfect and the active materials cannot be well connected. Graphene is a typical two-dimensional sheet structure, and carbon is sp 2 Hybridization participates in bonding and interconnects to form a two-dimensional lattice plane based on the hexagonal structure. In the direction perpendicular to the plane, there is a delocalized electron cloud formed by the electrons provided by each carbon atom, which can increase the contact area with the electrode active material particles, thereby improving the conductivity. Because graphene is a two-dimensional conductive network structure material, combined with zero-dimensional conductive carbon black, it can fill and connect the gaps between active material particles and remote particles well, constructing a more compact and effective conductive network structure. The principle of using graphene as a conductive agent is the excellent electron transmission ability brought about by its special structure with a two-dimensional high specific surface area. The conductive agent of the present invention, as a short-range conductive agent, mainly improves the electron conduction between adjacent active material particles. The introduction of the two-dimensional conductive agent graphene and the construction of a composite conductive network can simultaneously improve the conduction rate of electrons in the electrode, reduce internal resistance, and thus improve the rate performance.
[0033] The method for preparing the positive electrode of the sandwich structure hybrid capacitor according to the embodiment of the present invention comprises the following steps: S1: uniformly coating the first slurry on the surface of the current collector to form a first slurry layer with a coating thickness of 30-50 μm; S2: uniformly coating the second slurry on the surface of the first slurry layer to form a second slurry layer with a coating thickness of 50-80 μm; S3: The first slurry is uniformly coated on the surface of the second slurry layer again, with a coating thickness of 30-50 μm, to complete single-sided coating; S4: Repeat the above steps S1 to S3 to coat the other side of the current collector to obtain a positive electrode sheet with a sandwich structure coated on both sides; S5: The obtained double-sided coated sandwich structure positive electrode sheet is vacuum dried at 80° C. for 3 h, and the thickness of the positive electrode sheet is rolled to 100-200 μm at a pressure of 5-20 MPa to obtain a hybrid capacitor positive electrode with a composite sandwich structure.
[0034] During the drying process, since the density of activated carbon is much lower than that of LiNi 0.5 Co 0.2 Mn 0.3 O 2, causing the activated carbon particles in the slurry coating after coating to tend to float on the electrode surface. In addition, due to capillary forces, the binder and carbon black will migrate to the surface as the solvent evaporates, resulting in a concentration gradient inside the electrode, especially during high-speed baking. By regulating the gradient distribution of the porous structure of the electrode, a high-porosity structure in the upper layer and a high-density structure in the lower layer are achieved. The special structure of the electrode and the reasonable porosity distribution are conducive to the migration of lithium ions inside the thick electrode, perfectly balancing the dual cores of high energy density and super-fast charging.
[0035] As an embodiment, the first slurry is prepared according to the following steps: S11: Bake the powder of the nano single crystal positive electrode material and the first conductive agent at 120° C. for more than 8 hours before use to ensure accurate weight measurement; S12: Weigh 84-96 parts of nano single crystal positive electrode material and 1-3 parts of first graphene by mass to form active material mixture A; S13: dissolving the first binder (polyvinylidene fluoride, PVDF) with N-methylpyrrolidone (NMP), stirring and dispersing, and evacuating to a transparent solution for standby use; S14: Add the first conductive agent to the solution and stir at high speed for 2-3 hours (; S15: Add active material mixture A three times and disperse at high speed for 4-6 hours to prepare a first slurry, pass through a 200-mesh sieve, and set aside.
[0036] As an embodiment, the second slurry is prepared according to the following steps: S21: baking the carbon material and the second conductive agent powder at 140° C. for more than 4 hours before use to ensure accurate weight measurement; S22: Weigh 80-90 parts of carbon material and 1-5 parts of second graphene by mass to form an active material mixture B; S23: Weigh 5 to 8 parts of the second binder, add it to pure water, and place it in a mixer for dispersion (speed 100 to 500 r / min), at a speed of 100 to 500 r / min, until the second binder is completely dispersed in the water; S24: Add the second conductive agent, soak it evenly at a low speed, and then disperse it at a high speed for 2 hours; S25: Add active material mixture B gradually in three times and disperse and stir at high speed for 4-6 hours (the circulating water temperature controls the slurry temperature); S26: The second slurry is configured to pass through a 200-mesh sieve for standby use. Example 1
[0037] The positive electrode of the hybrid capacitor in this embodiment is made of lithium iron phosphate (LiFePO 4), the second slurry uses activated carbon (AC), which specifically includes the following steps: Lithium iron phosphate (LiFePO 4 ) Preparation of slurry: Weigh 94 parts by mass of lithium iron phosphate (LiFePO 4 ), 2 parts of polyvinylidene fluoride (PVDF), 2 parts of conductive carbon black (SP), and 2 parts of the first graphene were baked in an oven at 120°C for more than 8 hours; then LiFePO 4 The active material and the first graphene are mixed in a double planetary vacuum mixer to form an active material mixture A; an appropriate amount of N-methylpyrrolidone (NMP) is added to the mixer, and PVDF is slowly added, stirred and dispersed, and vacuumed until transparent and free of bubbles; SP is added to an organic solvent and dispersed at high speed for 2 to 3 hours; then the active material mixture A is slowly added in three times, and dispersed at high speed for 4 to 6 hours to form LiFePO 4 The first slurry is passed through a 200-mesh sieve and set aside.
[0038] Preparation of activated carbon (AC) slurry: 90 parts of activated carbon (AC), 3 parts of conductive carbon black (SP), 5 parts of polyvinylidene fluoride (PVDF), and 2 parts of second graphene were weighed by mass and baked in an oven at 140°C for more than 4 hours; then the AC active material and the second graphene were mixed in a double planetary vacuum mixer to form an active material mixture B; LA132 (Sichuan Yindile) was slowly added to the mixer, and then an appropriate amount of pure water was added, and the mixture was stirred and dispersed, and vacuumed until there was no agglomeration; SP was added to the solvent and infiltrated evenly at a low speed, and then dispersed at a high speed for 2 hours; then the active material mixture B was slowly added in three times, and the mixture was dispersed and stirred at a high speed for 4h~6h, and passed through a 200-mesh sieve to prepare the AC second slurry for use.
[0039] Preparation of hybrid capacitor with sandwich structure positive electrode: The first slurry is evenly coated on the current collector with a coating thickness of 30 μm; the second slurry is evenly coated on the surface of the first slurry layer with a coating thickness of 80 μm; the first slurry is evenly coated on the surface of the second slurry layer again with a coating thickness of 30 μm; after single-sided coating and drying, the above steps are repeated for back-side coating and drying, vacuum drying at 80°C for 3 hours, and roller pressing is performed to obtain a hybrid capacitor positive electrode with a composite sandwich structure. Example 2
[0040] The positive electrode of the hybrid capacitor in this embodiment is made of lithium iron phosphate (LiFePO 4 ), the second slurry uses activated carbon (AC), which specifically includes the following steps: (1) Using the same method as steps (1) and (2) in Example 1, lithium iron phosphate (LiFePO 4) slurry and activated carbon (AC) slurry; (2) Preparation of sandwich structure positive electrode for hybrid capacitor: The first slurry is evenly coated on the current collector with a coating thickness of 35 μm, and it is placed in an oven at 100°C for rapid drying before being taken out; the second slurry is evenly coated on the surface of the first slurry layer with a coating thickness of 70 μm, and it is placed in an oven at 100°C for rapid drying before being taken out; the first slurry is evenly coated on the surface of the second slurry layer again with a coating thickness of 35 μm, and it is placed in an oven at 100°C for rapid drying; after single-sided coating and drying, the above steps are repeated for back-side coating and drying, and after vacuum drying at 80°C for 3 hours, a composite sandwich structure of a hybrid capacitor positive electrode is obtained by roller pressing. Example 3
[0041] The positive electrode of the hybrid capacitor in this embodiment is made of lithium iron phosphate (LiFePO 4 ), the second slurry uses activated carbon (AC), which specifically includes the following steps: (1) Using the same method as steps (1) and (2) in Example 1, lithium iron phosphate (LiFePO 4 ) slurry and activated carbon (AC) slurry; Preparation of hybrid capacitor with sandwich structure positive electrode: The first slurry is evenly coated on the current collector with a coating thickness of 45 μm; the second slurry is evenly coated on the surface of the first slurry layer with a coating thickness of 50 μm; the first slurry is evenly coated on the surface of the second slurry layer again with a coating thickness of 45 μm; after single-sided coating and drying, the above steps are repeated for back-side coating and drying, vacuum drying at 80°C for 3 hours, and roller pressing is performed to obtain a hybrid capacitor positive electrode with a composite sandwich structure. Example 4
[0042] The positive electrode of the hybrid capacitor in this embodiment is made of high nickel ternary (LiNi 8 CoMnO 2 ), the second slurry uses activated carbon (AC), which specifically includes the following steps: (1) High nickel ternary (LiNi 8 CoMnO 2 The preparation method of the first slurry is the same as that of step (1) in Example 1, except that the active material lithium iron phosphate (LiFePO 4 ) replaced with high nickel ternary (LiNi 8 CoMnO 2 ); The activated carbon (AC) slurry was prepared by the same method as step (2) in Example 1; (3) Preparation of sandwich structure positive electrode for hybrid capacitor: The first slurry is evenly coated on the current collector with a coating thickness of 30 μm; the second slurry is evenly coated on the surface of the first slurry layer with a coating thickness of 80 μm; the first slurry is evenly coated on the surface of the second slurry layer again with a coating thickness of 30 μm; after single-sided coating and drying, the above steps are repeated for back-side coating and drying, vacuum drying at 80°C for 3 hours, and roller pressing is performed to obtain a hybrid capacitor positive electrode with a composite sandwich structure. Example 5
[0043] The positive electrode of the hybrid capacitor in this embodiment is made of high nickel ternary (LiNi 8 CoMnO 2 ), the second slurry uses activated carbon (AC), which specifically includes the following steps: (1) The same method as steps (1) and (2) in Example 4 was used to prepare high nickel ternary (LiNi 8 CoMnO 2 ) slurry and activated carbon (AC) slurry; (2) Preparation of sandwich structure positive electrode for hybrid capacitor: The first slurry is evenly coated on the current collector with a coating thickness of 35 μm; the second slurry is evenly coated on the surface of the first slurry layer with a coating thickness of 70 μm; the first slurry is evenly coated on the surface of the second slurry layer again with a coating thickness of 35 μm; after single-sided coating and drying, the above steps are repeated for back-side coating and drying, vacuum drying at 80°C for 3 hours, and roller pressing is performed to obtain a hybrid capacitor positive electrode with a composite sandwich structure.
[0044] The test data of the hybrid supercapacitor using the positive electrode of the hybrid capacitor of this embodiment are as follows: Figure 1~Figure 4 shown. Example 6
[0045] The positive electrode of the hybrid capacitor in this embodiment is made of high nickel ternary (LiNi 8 CoMnO 2 ), the second slurry uses activated carbon (AC), which specifically includes the following steps: (1) The same method as steps (1) and (2) in Example 4 was used to prepare high nickel ternary (LiNi 8 CoMnO 2 ) slurry and activated carbon (AC) slurry; (2) Preparation of sandwich structure positive electrode for hybrid capacitor: The first slurry is evenly coated on the current collector with a coating thickness of 45 μm; the second slurry is evenly coated on the surface of the first slurry layer with a coating thickness of 50 μm; the first slurry is evenly coated on the surface of the second slurry layer again with a coating thickness of 45 μm; after single-sided coating and drying, the above steps are repeated for back-side coating and drying, vacuum drying at 80°C for 3 hours, and roller pressing is performed to obtain a hybrid capacitor positive electrode with a composite sandwich structure.
[0046] The coating thickness of Example 1 to Example 6 is shown in Table 1: Table 1
[0047] Comparative Example This comparative example uses conventional activated carbon (AC) as the capacitor positive electrode material, and specifically comprises the following steps: preparing activated carbon (AC) slurry by the same method as step (2) in Example 1, coating a single activated carbon slurry on both sides of the current collector, with a single-side coating thickness of 140 μm, and rolling to obtain a conventional capacitor positive electrode.
[0048] Using 5C constant current and constant voltage charging, 5C constant current discharge, and a voltage range of 2.5~4.2V, the initial performance of the cylindrical monomer is shown in Table 2: Table 2
[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A sandwich structured hybrid capacitor positive electrode, comprising a current collector, characterized in that: The first slurry layer, the second slurry layer, and the first slurry layer are sequentially coated on the current collector, wherein: The first slurry of the first slurry layer includes the following components by mass: 84-96 parts of nano single crystal positive electrode material, 1-3 parts of first graphene, 1-6 parts of first conductive agent and 2-7 parts of first binder; The second slurry of the second slurry layer includes the following components in parts by mass: 80-90 parts of carbon material, 1-5 parts of second graphene, 4-7 parts of second conductive agent and 5-8 parts of second binder.
2. The positive electrode of the hybrid capacitor with a sandwich structure as claimed in claim 1, characterized in that: Nano single crystal cathode materials include LiFePO4, LiCoO2, LiNi x Co y Mn z O2、LiNi x Co y Al z One or more of O2, x+y+z=1, 0.2≤x≤0.95, 0.05≤y≤0.4, 0.05≤z≤0.
5.
3. The positive electrode of the hybrid capacitor with a sandwich structure as claimed in claim 1, characterized in that: The first graphene and the second graphene both have a specific surface area of 400 to 2000 m 2 / g of graphene.
4. The positive electrode of the hybrid capacitor with a sandwich structure as claimed in claim 3, characterized in that: The first graphene of the first slurry is coated on the outside of the nano single crystal positive electrode material, and the second graphene of the second slurry is coated on the outside of the carbon material.
5. The positive electrode of the hybrid capacitor with a sandwich structure as claimed in claim 4, characterized in that: The first graphene is microporous graphene, the second graphene is macroporous graphene, and the pores of the first graphene are smaller than the pores of the second graphene.
6. The positive electrode of the hybrid capacitor with a sandwich structure as claimed in claim 4, characterized in that: The coating thickness of the first graphene and the second graphene are both less than 1000nm.
7. The sandwich structure hybrid capacitor positive electrode according to claim 1, characterized in that: The first conductive agent and the second conductive agent are acetylene black, conductive carbon black or carbon nanotubes, the first binder is polyvinylidene fluoride, the second binder is a mixture of one or more of styrene-butadiene rubber, acrylonitrile multipolymer and polytetrafluoroethylene, and the current collector is carbon-coated aluminum foil or corroded aluminum foil.
8. A method for preparing a positive electrode of a sandwich structure hybrid capacitor, characterized in that: The following steps are involved: S1: uniformly coating the first slurry on one side of the current collector to form a first slurry layer with a coating thickness of 30-50 μm; S2: uniformly coating the second slurry on the surface of the first slurry layer to form a second slurry layer with a coating thickness of 50-80 μm; S3: The first slurry is uniformly coated on the surface of the second slurry layer again, and the coating thickness is 30-50 μm; S4: Repeat steps S1 to S3 to coat the other side of the current collector to obtain a positive electrode sheet with a sandwich structure coated on both sides; S5: The obtained double-sided coated sandwich structure positive electrode sheet is vacuum dried at 80° C. for 3 h, and the thickness of the positive electrode sheet is rolled to 100-200 μm at a pressure of 5-20 MPa to obtain a hybrid capacitor positive electrode with a composite sandwich structure.
9. The method for preparing a positive electrode of a hybrid capacitor with a sandwich structure as claimed in claim 8, characterized in that: The first slurry was prepared according to the following steps: S11: Bake the powder of the nano single crystal positive electrode material and the first conductive agent at 120° C. for more than 8 hours before use to ensure accurate weight measurement; S12: Weigh 84-96 parts of nano single crystal positive electrode material and 1-3 parts of first graphene by mass to form active material mixture A; S13: dissolving the first binder with N-methylpyrrolidone, stirring and dispersing, and evacuating the mixture to a transparent solution for standby use; S14: adding the first conductive agent to the solution and dispersing at high speed for 2-3 hours; S15: Add active material mixture A three times, disperse and stir at high speed for 4-6 hours to prepare a first slurry, and pass through a 200-mesh sieve for later use.
10. The method for preparing a positive electrode of a hybrid capacitor with a sandwich structure as claimed in claim 8, characterized in that: The second slurry was prepared according to the following steps: S21: baking the carbon material and the second conductive agent powder at 140° C. for more than 4 hours before use to ensure accurate weight measurement; S22: Weigh 80-90 parts of carbon material and 1-5 parts of second graphene by mass to form an active material mixture B; S23: Weigh 5 to 8 parts of the second binder, add it to pure water, and disperse it in a mixer at a speed of 100 to 500 r / min until the second binder is completely dispersed in the water; S24: Add the second conductive agent, soak evenly at low speed, and disperse at high speed for 2h; S25: Add active material mixture B gradually in three times and disperse at high speed for 4-6 hours; S26: The second slurry is configured to pass through a 200-mesh sieve for standby use.